MEMBANGUN MASYARAKAT HUKUM YANG BERADAB MELALUI PENDIDIKAN INTEGRAL BERBASIS AGAMA - Yogi Prasetyo (MUADDIB Jurnal Kependidikan dan Keislaman, 2015)
The rapid time development is also followed by the human science development. However, problems arise in human life when the science development is not matched by a strong religious base, so it willgive brith the man whom has no humanities and divinity. Education only cultivate the human mind and constrict qolbu (hearth) role as God's gift that does not need to be doubtful.Education is only meant an empirical and concrete science that can be accepted by the senses, beyond that is not considered as science. The dichotomy of this education will only give birth to a smart man but uncivilized.Unlawful and some crimes now are doneby educated man, not the stupid and not knowledgableman. Such as corruption, money politics, bribery, abuse of office, drugs, human rights violations, immorality, violence, harassment, electronic crime and other various unlawful acts, were all done by an educated man.For those, we need an integral education based on religion, so that people can use his knowledge on the God. If education could provide a balance in human life, there will be a life where people awake from unlawful acts. Because religion is essentially the rule that contains the commands and prohibitions for humans. So, obeying religion is also a form of obedience to the law. Religion of God must teach goodness which is certainly followed by national laws. Because Indonesia is a religious law states, so the law is executed based on the religious values. With this integral education, peoples life will be more law-abiding and civilized.